Isolation and characterization of a novel bacterium growing via reductive dehalogenation of 2-chlorophenol. - Cole, J R (1994)
A bacterium capable of anaerobic growth via reductive dehalogenation of 2-chlorophenol was isolated from a culture enriched from sediment taken from a small stream near Lansing, Mich. The organism, designated strain 2CP-1, is a gram-negative rod ca. 3 by 0.5 micron in size and is a catalase-negative, oxidase-negative, facultative anaerobe that forms small red colonies in anaerobic media. The organism grew in reduced anaerobic mineral medium supplemented with 2-chlorophenol, acetate, and vitamins, producing phenol as a product. It did not grow when either 2-chlorophenol or acetate was omitted. The growth yield was about 3 g of protein per mol of 2-chlorophenol dechlorinated, and the doubling time was 3.7 days. Only the ortho position was dehalogenated, and additional chlorines at other positions decreased or blocked ortho dechlorination. The organism also grew with fumarate as its electron acceptor. Dechlorination activity is inducible, since cultures grown in fumarate containing medium with 2-chlorophenol rapidly dechlorinated additional 2-chlorophenol, while cultures grown in the same medium without 2-chlorophenol did not. Analysis of the organism's 16S rRNA sequence revealed that it is a member of the delta proteobacteria, more closely related to the myxobacteria than to the sulfidogenic bacteria.